Postsurgical pain management among obstetrics and gynecology patients in a teaching hospital in Tabriz, Iran: a best practices implementation project. Issue 4 (14th December 2022) - Hajebrahimi, Sakineh; Vaezi, Maryam; Moslemi Tabrizi, Farnaz; Asghari Khatooni, Azam; Zahed, Khadijeh
ABSTRACT: Objectives: The purpose of this project was to improve the compliance of patients' pain management process after surgery using evidence-based criteria at the Al-Zahra Educational Hospital in Tabriz. Introduction: Reducing and relieving pain are among the basic rights of patients, and the management of this component should be one of the basic goals of the patient care team. Inadequate pain control can have many unpleasant consequences for the patient and increase hospital costs. Due to the importance of pain control and a gap in this area, it was decided to implement a project to improve pain control in postoperative patients grounded in evidence-based recommendations. Method: This project was carried out at a Level III hospital in Iran from December 2019 to June 2020. A baseline audit, based on the JBI Practical Application of Clinical Evidence-Based System (JBI PACES) and Getting Research into Practice (GRiP) audit and feedback tool was conducted with 40 patients in the surgery ward of the hospital. After developing the GRiP table (barriers, strategy, resources and outcome), a follow-up audit was done three times. The different stages of the audit were centered in evidence-based criteria. At each stage of follow-up, 40 patients were randomly selected in the postoperative stage. Results: At the baseline audit, out of a total of eight criteria, only criterion 2 corresponded to the audit criteria where there was no pain assessment tool or protocol for pain or for training patients and nurses. Over the three follow-up audits, 100% improvement was achieved in half of the criteria through preparing visual analogue scale pain instruments, and development of a pain protocol and a pain self-care protocol, and a 63% improvement was observed in one of the criteria. Patients' pain decreased from very severe to mild/moderate in the first few hours in 70% of patients after surgery. Conclusion: The use of this best practices implementation project led to the improvement of the postoperative pain management process of patients and the improvement of patient care quality. The use of the JBI Method is recommended to address other current or defective hospital processes.